Modeling carbon dioxide removal via sinking of particulate organic carbon from macroalgae cultivation - Chen, Si; Strong-Wright, Jago; Taylor, John R. (Frontiers in Marine Science, 2024)
Macroalgae cultivation is receiving growing attention as a potential carbon dioxide removal (CDR) strategy. Macroalgae biomass harvesting and/or intentional sinking have been the main focus of research efforts. A significant amount of biomass is naturally lost through erosion and breakage of cultivated or naturally growing seaweed, but the contribution of the resulting particulates to carbon sequestration is relatively unexplored. Here, we use a fully coupled kelp-biogeochemistry model forced by idealized parameters in a closed system to estimate the potential of macroalgal-derived particulate organic carbon (POC) sinking as a CDR pathway. Our model indicates that at a kelp density of 1.1 fronds m -3 , macroalgal POC sinking can export 7.4 times more carbon to the deep sea (depths > 500m) and remove 5.2 times more carbon from the atmosphere (equivalent to an additional 336.0 gC m -2 yr -1 ) compared to the natural biological pump without kelp in our idealized closed system. The results suggest that CDR associated with POC sinking should be explored as a possible benefit of seaweed farming and point to the need for further study on organic carbon partitioning and its bioavailability to quantify the effectiveness and impacts of macroalgal cultivation as a CDR strategy.